Method for simulating processes of processing inhomogeneous data in buffer drives of routers - P. S. Chernyavski (Системный анализ и прикладная информатика, 2021)
The article proposes a method for modeling the processing of heterogeneous data in the buffer storage of routers. In contrast to the existing approaches, in the developed method, in the analytical description of the processes of functioning of buffer storage devices of routers under the influence of heterogeneous traffic of subscribers of a special-purpose communication network, the apparatus of the theory of cellular automata was used, which made it possible to take into account the probability of timely processing of data of all used priority levels of communication directions.As a result of the experiment carried out on the basis of a real special communication network, it was found that the developed method of modeling the processes of processing inhomogeneous data of buffer storage devices of routers makes it possible to increase the accuracy of determining the probability of timely delivery of priority information to subscribers of a special purpose communication network, in comparison with the existing standardized methods.